Screening of spices for antimicrobial activity - BANERJEE, MINAKSHI DE, AMIT KRISHNA DE, ARUN BARAN (Journal of Spices and Aromatic Crops, 1999)
Thirty five spices were screened for their antimicrobial activity against Bacillus subtilis, Escherichia coli and Saccharomyces cerevisiae. The results indicated that clove, cinnamon, bishop’s weed, chilli, horse raddish, cumin, tamarind, black cumin, pomegranate seeds, nutmeg, garlic, onion, tejpat, celery and cambodge had potent antimicrobial properties.